The Role of Lung Function Testing in Newborn Infants With Congenital Thoracic Arterial Anomalies - Claudia Columbo; Francesca Landolfo; Domenico Umberto De Rose; Anna Claudia Massolo; Aurelio Secinaro; Teresa Pia Santangelo; Marilena Trozzi; Cosimo Marco Campanale; Alessandra Toscano; Irma Capolupo; Pietro Bagolan; Andrea Dotta (Frontiers Media S.A., 2021)
Introduction: Congenital thoracic arterial anomalies (CTAAs), such as complete or incomplete vascular rings, pulmonary artery sling, and innominate artery compression syndrome, may cause severe tracheomalacia and upper airway obstruction. An obstructive ventilatory pattern at lung function testing (LFT) has been suggested in the presence of CTAA. The severity of obstruction may be evaluated by LFT. Little is known about the use of LFT in newborn infants with CTAA. The aim of our study is to evaluate the role of LFT in CTAA diagnosis.Methods: This is a retrospective study, conducted between February 2016 and July 2020. All CTAA cases for whom LFT was performed preoperatively were considered for inclusion. Tidal volume (Vt), respiratory rate, and the ratio of time to reach the peak tidal expiratory flow over total expiratory time (tPTEF/tE) were assessed and compared to existing normative data. Demographics and CTAA characteristics were also collected.Results: Thirty cases were included. All infants with CTAA showed a significantly reduced Vt and tPTEF/tE, compared to existing normative data suggesting an obstructive pattern.No significant differences were found for LFT between cases with a tracheal obstruction <50% compared to those with tracheal obstruction ≥50%, or between cases with and without symptoms. Sixteen infants (53.3%) had respiratory symptoms related to CTAA. Of these, only two cases had also dysphagia.Conclusion: LFT values were significantly reduced in cases with CTAA before surgery. LFT represents a potential feasible and non-invasive useful tool to guide diagnosis in the suspect of CTAA.